Trypanosomiasis: Recent advances in strategies for control - Omowumi T Kayode; Charity K Lele; Abolanle AA Kayode (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2020)
Trypanosomiasis is numbered among the list of seventeen transmissible diseases and is associated with poor socio-economic status. Trypanosomiasis is referred to as a neglected tropical disease (NTDs) by the World Health Organization, due to its limited diagnostic and treatment development, with yet poor control measures. Three diseases of parasitic origin emanate due to genetically connected protozoa, trypanosomatid and kinetoplastida. They are the basis of many public health challenges in the less developed world and include American Trypanosomiasis (Chagas disease), Human African Trypanosomiasis and Leishmaniasis. This review emphasizes Trypanosomiasis in general, the lifecycle, biochemistry of parasite infection, disease treatment and management. Prevention options, the biochemistry of drug resistance and novel treatment of disease are among subjects considered.